Streamlined Poststroke Treatment Order Sets During the SARS-CoV-2 Pandemic: Simplifying While Not Compromising Care. Issue 10 (October 2020) - Gioia, Laura C.; Poppe, Alexandre Y.; Laroche, Roxanne; Dacier-Falque, Tristan; Sévigny, Isabelle; Daneault, Nicole; Deschaintre, Yan; Jacquin, Grégory; Stapf, Christian; Odier, Celine
Abstract : Background and Purpose: Standard poststroke treatment monitoring protocols are made problematic during the coronavirus disease 2019 (COVID-19) pandemic by the frequency of patient assessments, requiring repeated donning and doffing procedures in a short interval of time. Methods: A streamlined poststroke treatment protocol was developed to limit frequency of patient encounters while maximizing the yield of each encounter by grouping together different components of poststroke care into single bedside visits. Results: Streamlined order sets were developed late March 2020. During the first 6 weeks following implementation, 70 patients were admitted to a geographically defined designated warm COVID-19 unit with modified poststroke care order sets. Of these, 33 (47.1%) patients received acute reperfusion therapy. All but 3 patients evolved favorably with either stable or improving National Institutes of Health Stroke Scale at 24 hours. In the 3 patients who experienced early neurological deterioration, none were found to be attributable to insufficient patient monitoring. Conclusions: Adapting preexisting poststroke care protocols may be necessary while the risk of COVID-19 infection remains high. We propose a streamlined approach to facilitate poststroke monitoring in patients with stroke with unknown COVID status.